Dialogues with Contemporary Political Theorists
XVII, 225 p.
Keywords: A lively and engaging collection which explains the various strands of political theory, identifies key futures trends and explores the foundations of contemporary debate. Features interviews with pre-eminent theorists, including Quentin Skinner, Carole Pateman and Alex Honneth.